Histopathological Features of Primary Nephrotic Syndrome in Children - M P Damanik; N Yoshikawa (Paediatrica Indonesiana, 1998)
Â Renal biopsy was performed on 28 out of 50 children with primary nephrotic syndrome encountered during the period January 1994 - December 1995. Light microscope (LM) and immunofluorescence microscope QM) examinations were performed on all biopsy specimens. LM examination indicated minimal changes (MC) in 13 cases (46.4%), focal segmental glomerulosclerosis (FSGS) in 10 (35.7%), membranous glomerulonephritis (MG) in 2 (7.1%), mesangial proliferative glomerulonephritis (MPG) in 7 (7.1 %), and membranoproliferative glomerulonephritis (MPGN) in 1 (3.6%). On IM examination, immunoglobulin deposit was not detected in any MC patients, whereas in FSGS, lgG, lgM, C3 and fibrinogen deposits were found. In the MG group, IgG deposition was detected in one case. In the MPG cases, depositions of lgA, IgG, lgM, C3 and fibrinogen were detected and in the case of MPGN, deposits of lgM and C3 were found. Regarding to response to steroid treatment in the MC group, there was a significant difference between the steroid sensitive and steroid insensitive (p<0.05). For the FSGS abnormality in the steroid treatment of U1e insensitive patients, there was found significant difference with the steroid sensitive abnormality (p<0.05). In conclusion, nephritic symptoms (hematuria, proteinuria, azothemia) are possibly the non minimal group and hence, it would be necessary to carry out renal biopsy to prove this.